2020
DOI: 10.1007/s42452-020-03730-x
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolytic biochars from sunflower seed shells, peanut shells and Spirulina algae: their potential as soil amendment and natural growth regulators

Abstract: Several studies have shown that pyrolysis conditions and feedstocks are the key factors influencing biochar chemical and physical properties. The information on the nature of biochar is quite important, especially when this carbonaceous material is intended to be used as a potential soil amendment. In this study, we investigated the formation and characterisation of biochars produced from vacuum pyrolysis of sunflower seed shells (SSS), peanut shells (PS) and Spirulina algae (Sp) at 280 °C (for SSS, PS and Sp)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 81 publications
0
4
0
1
Order By: Relevance
“…In this sense, biochar from sunflower seed shells, peanut shells and Spirulina algae were tested separately in lettuce. The results showed that when peanut shells were used (pyrolysis at 280 • C) it did not affect germination and exhibited a remarkable growthpromoting effect on the roots and stems of lettuce, as the presence of carbonyl derivatives and aromatics in the water-extractable substances of peanut shell biochar may be linked to the stimulating effects of this extract [87]. In contrast, the water-extractable substances from the biochar of both bio-waste produced at 350 • C inhibited the growth of lettuce, posing a risk of direct application as soil amendment.…”
Section: Bio-based Fertilizers Applied In Crops and Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, biochar from sunflower seed shells, peanut shells and Spirulina algae were tested separately in lettuce. The results showed that when peanut shells were used (pyrolysis at 280 • C) it did not affect germination and exhibited a remarkable growthpromoting effect on the roots and stems of lettuce, as the presence of carbonyl derivatives and aromatics in the water-extractable substances of peanut shell biochar may be linked to the stimulating effects of this extract [87]. In contrast, the water-extractable substances from the biochar of both bio-waste produced at 350 • C inhibited the growth of lettuce, posing a risk of direct application as soil amendment.…”
Section: Bio-based Fertilizers Applied In Crops and Soilmentioning
confidence: 99%
“…In contrast, the water-extractable substances from the biochar of both bio-waste produced at 350 • C inhibited the growth of lettuce, posing a risk of direct application as soil amendment. In this case, aromatics may be responsible for growth inhibition in the water-extractable substances of the biochar from the sunflower seed shells, while the organic nitrogen compounds would enhance the inhibitory effect in the water-extractable substances of the biochar of the Spirulina algae [87].…”
Section: Bio-based Fertilizers Applied In Crops and Soilmentioning
confidence: 99%
“…Root lengths were also measured for each sample. A germination index of at least 50% is required for use in the soil [43]. A seed was considered physiologically germinated if the radicle was longer than 2 mm.…”
Section: Phytotoxicity Testmentioning
confidence: 99%
“…In addition, different pyrolysis types for biochar production from algal biomass were investigated. Silva et al (2020) produced biochar with 43% yield by fast pyrolysis (residence time: 1 min) of Spirulina (blue green micro-algae grown in alkaline water) at 280 C. A yield of biochar from fast pyrolysis (43%) was obtained more than that of slow pyrolysis (36%).…”
Section: Biochar Production From Various Feedstockmentioning
confidence: 99%